The Concept of Justice In the System of the Confliction Through Contextualization of Surah al-Mā’ida 44-47 (Application of Abdullah Saeed’s Contextual Approach) - Nafisatul Mu'awwanah (Universitas Islam Negeri Mataram, 2018)
This article aims to employ Abdullah Saeed’s contextual approach to explore the concept of justice in the system of the confliction based on the interpretation of surah al-Mā'ida: 44-47. Based on this approach, a contextualist must be able to find two meanings that arise from the interpreted verse, i.e. meaning for the first recipient (historical meaning) and meaning for the present context (contemporary meaning). For the first recipient of surah al-Mā'ida: 44-47, it is understood as a form of justice and equality of the Prophet in mediating the case of the dispute at that time, especially between the Naḍīr and the Qurayẓa tribe. When this verse is attributed to the form of the present state of the constitutional system, the contemporary meaning of this verse is that a state is capable of mediating fairly among its people in order to avoid the clash between rights and obligations. In this case, the form of the state, secular or non-secular, cannot be taken as a measure of the state system in accordance with this verse.